Dysfunctional Attitudes Lead to Depressive Symptoms by Generating Subjective Stress. Issue 3 (2nd April 2016) - Kuroda, Yuji
ABSTRACT: Previous studies have indicated that objective stress—negative events that have actually occurred outside of individuals—is involved in processes of dysfunctional attitudes leading to depression. Subjective stress—individuals' perception of negative events that have not actually occurred outside of them—is also predicted to be involved in these processes. However, few studies have empirically investigated this prediction. The primary purpose of this study was to fill this gap by testing the hypothesis that dysfunctional attitudes lead to depression by generating subjective stress. A longitudinal design was employed and initial depression was controlled. The results supported the hypothesis. It was also found that initial depression fostered subsequent depression by generating subjective stress. This study contributes to the literature on depression mechanisms by elucidating that subjective stress plays an important role in the development and exacerbation of depression. This study also has important clinical implications as it suggests that preventing subjective stress in individuals with dysfunctional attitudes or depression helps to protect the development or exacerbation of their depression.